2012
DOI: 10.21608/eajbsz.2012.13874
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of ginseng plant extract (ginsana) and garlic powder against the bad effects of lambda-cyhalothrin insecticide on kidneys of female rats

Abstract: Ginseng and garlic are well known plants which have anti oxidant effects. The present study investigates the protective effects of ginseng extract and garlic powder on the bad effects of lambda-cyhalothrin insecticides (LTC). Eighty female Wister rats divided into 4 groups as follow; group (1) control group, group (2) injected with(9.3 mg/kg b.wt) LTC alone, group (3) injected with(200 mg/kg b.wt) ginseng extract (G115) followed by (9.3 mg/kg b.wt) LTC, group (4) injected with (100 mg/kg b.wt) garlic extract (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…They reported that ginseng improved rat's tissues treated with ochratoxin. Mohi‐Eldin, Mostafa and Abd‐El Kader () evaluated the protective effects of ginseng plant extract against the toxicity of lambda‐cyhalothrin insecticide on kidneys of female rats. They found that ginseng administration reduced the oedema of bowman's space, cloudy swelling and necrosis in the kidney tissues.…”
Section: Changes In Some Blood Biochemical Parameters Of Nile Tilapiamentioning
confidence: 99%
“…They reported that ginseng improved rat's tissues treated with ochratoxin. Mohi‐Eldin, Mostafa and Abd‐El Kader () evaluated the protective effects of ginseng plant extract against the toxicity of lambda‐cyhalothrin insecticide on kidneys of female rats. They found that ginseng administration reduced the oedema of bowman's space, cloudy swelling and necrosis in the kidney tissues.…”
Section: Changes In Some Blood Biochemical Parameters Of Nile Tilapiamentioning
confidence: 99%